2005
DOI: 10.1634/stemcells.2004-0340
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Endothelial Progenitor Cells Accelerates Dermal Wound Healing with Increased Recruitment of Monocytes/Macrophages and Neovascularization

Abstract: Endothelial progenitor cells (EPCs) act as endothelial precursors that promote new blood vessel formation and increase angiogenesis by secreting growth factors and cytokines in ischemic tissues. These facts prompt the hypothesis that EPC transplantation should accelerate the wound-repair process by facilitating neovascularization and the production of various molecules related to wound healing. In a murine dermal excisional wound model, EPC transplantation accelerated wound re-epithelialization compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
135
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(142 citation statements)
references
References 31 publications
5
135
1
1
Order By: Relevance
“…EPCs and OECs each provided benefit when delivered individually, but together they provided a greater benefit in this particular model of PAD. These results suggest this approach will be useful to treat cardiac infarction (44), and other situations in which vascularization is lacking (e.g., wound healing) (45). More broadly, this may provide a core technology for the entire field of regenerative medicine, because of the need to create new vascular beds in most situations of regeneration and tissue engineering (16).…”
Section: Discussionmentioning
confidence: 99%
“…EPCs and OECs each provided benefit when delivered individually, but together they provided a greater benefit in this particular model of PAD. These results suggest this approach will be useful to treat cardiac infarction (44), and other situations in which vascularization is lacking (e.g., wound healing) (45). More broadly, this may provide a core technology for the entire field of regenerative medicine, because of the need to create new vascular beds in most situations of regeneration and tissue engineering (16).…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis is initially induced by tissue destruction and hypoxia and is subsequently stimulated by various molecules such as basic fibroblast growth factor, VEGF, and transforming growth factor-β, secreted by macrophages, keratinocytes, and endothelial cells. A role of EPCs in granulation tissue formation is directly suggested by experiments demonstrating that cell therapy with EPCs enhances wound healing in mice (Suh et al 2005). The release of various growth factors such as VEGF and platelet-derived growth factor by EPCs appears to enhance wound healing (Suh et al 2005).…”
mentioning
confidence: 99%
“…A role of EPCs in granulation tissue formation is directly suggested by experiments demonstrating that cell therapy with EPCs enhances wound healing in mice (Suh et al 2005). The release of various growth factors such as VEGF and platelet-derived growth factor by EPCs appears to enhance wound healing (Suh et al 2005). Reepithelialisation is the term used to describe the appearance of a new epithelial layer on top of a healing skin wound.…”
mentioning
confidence: 99%
“…44, 45 Suh and co-workers reported that human EPC obtained by Cells as vehicles for therapeutic genes J Prieto et al culturing in specific medium peripheral blood mononuclear cells and given to nude mice induced an acceleration of wound healing by local production of growth factors, stimulation of tissue repair and neovascularization. 46 In 2006, Taniguchi et al 47 showed that EPC obtained from human peripheral blood mononuclear cells or from murine BM after culture in specific medium for 10 days and given intrasplenically were able to ameliorate acute carbon tetrachloride liver damage in nude mice (human EPC) or in BALB/c mice (murine EPC) and to improve survival. They demonstrated that EPC generated high levels of hepatocyte growth factor, VEGF and heparin-binding EGF-like growth factor and stimulated the endogenous production of VEGF.…”
Section: Bone Marrow-derived Endothelial Progenitor Cells As Carriersmentioning
confidence: 99%